The outcome of Descemet membrane endothelial keratoplasty (DMEK) with different tamponade material. - Mohd Amin, Muhammad Hafiz As-Shaarani; Akhtar Ali, Ahmad Nurfahmi; Mohd. Kamal, Khairidzan; Salam, Adzura (2021)
OBJECTIVE: To compare the outcome of different tamponade material in Descemet membrane endothelial keratoplasty (DMEK).